2012
DOI: 10.4103/2156-7514.96543
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Aggressive Central Giant Cell Granuloma of Maxilla through Le Fort I Access Osteotomy

Abstract: Giant cell granuloma (GCG) is an uncommon bony lesion in the head and neck region, most commonly affecting the maxilla and mandible and has a female predilection. The clinical behavior of central GCG ranges from a slowly growing asymptomatic swelling to an aggressive lesion. The clinical, radiological, histological features and management of an aggressive GCG of maxilla in an 18-year-old female patient are described and discussed. It is emphasized that surgery is the traditional and still the most accepted tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…In agreement with Ahmad et al, 2016 (48) and Reddy. 2012 (29) But inconsistent with Manchanda et al, 2011 (49) who reported that surgical curettage of well-defined localized lesions is associated with a low rate of recurrence. Finally, traditional surgery of an aggressive CGCG was performed without lesion recurrence is attributed to small lesion size, early diagnosis, and high standard surgical curettage that is difficult in the maxillae.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In agreement with Ahmad et al, 2016 (48) and Reddy. 2012 (29) But inconsistent with Manchanda et al, 2011 (49) who reported that surgical curettage of well-defined localized lesions is associated with a low rate of recurrence. Finally, traditional surgery of an aggressive CGCG was performed without lesion recurrence is attributed to small lesion size, early diagnosis, and high standard surgical curettage that is difficult in the maxillae.…”
Section: Discussionmentioning
confidence: 96%
“…Root resorption and tooth displacement may also be evident. (29) Although radiographic features of CGCG are not pathognomonic. There were similar findings in the OPG view of our patient, which revealed well-defined periapical unilocular radiolucent area involving the apices 11 (FDI) and 12 (FDI) with no evidence of root resorption or tooth displacement.…”
Section: Discussionmentioning
confidence: 99%
“…It is more common in females. It usually appears in the mandibula and maxilla and sometimes displays a locally aggressive course (1)(2)(3). It is histologically defined as a non-encapsulated mass, including fibroblastic fusiform cells, multinuclear giant cells, and extravasated erythrocyte clusters.…”
Section: Discussionmentioning
confidence: 99%
“…It is seen more frequently in females than in males, and it presents in the first 3 decades of life (1,2). It is divided into two groups as peripheral and central lesions.…”
Section: Introductionmentioning
confidence: 99%